La estructuración lógica matemática en los adolescentes de 17 años: Desarrollo de una didáctica pertinente - Ordoñez Rodríguez, Miguel Ángel (2015)
The mind is in the most basic logic structure of the tennager , but to be understood have to use neuropsychology, who studies the neural part and the psychological part, which can break down the mind in systems, where is possible to find how it behaves logic within the mind. The development of the person, integrates a very important part of our study, this can determine how the adolescent process the information, from the perception to the structuring of new concepts. Also, you must to perform the study develops critical thinking that is used to give value judgments to all activities of the adolescent. And to determine the relationship between the mind and reality, as the relationship between the school and everyday life, as we seek to bring the academic theories to use in everyday life, especially knowledge of logic. The didactic is the method that seeks education, this work is focused on the game as the main educational resource, the confirmation of a sequence didactic where the mental game and the game of mathematical logic appears throughout the process; is more complicated and tedious for the teacher, but more educational for the student, the educational game helps the formation of the person in the course of life. And in adolescent mental and logical game can be used to implement the knowledge, adaptation to reality game teenager.